(untitled) (Spectrum, 2025)
This paper will explore the concept of de-territiorialization and its contribution to the re-imagining of the borderline concept of a nation into an alter-nation in Sam Selvon’s The Lonely Londoners (1956). In a post-WWII British context, Britain’s territorial space opened up as an opportunity for the influx of migrants even as it grappled with changes in policy-making, including the “British Nationality Act of 1948”. It allowed the migrants to frequently challenge the unity of Englishness against the backdrop of multiculturalism. Selvon’s novel focuses on the lives and the newly found ways of Caribbean migrants to adapt to post-WWII Britain. This paper will explore how de-territorialization as an idea prompted the English to re-conceptualize a nation as an alter-nation in Selvon’s novel. Spectrum, Volume 18, June 2023: 80-88